Peran Al dalam Takhrij Hadis Peluang dan Tantangan - Naysha Febriana; Rara Fitri Anjani; Muhammad Arifin Hsb; Farid Adnir (JOURNAL SAINS STUDENT RESEARCH, 2026)
The development of Artificial Intelligence (AI) has brought significant changes to various fields of knowledge, including Hadith studies. The application of AI in the process of Hadith takhrij has become an innovation that assists researchers in tracing Hadith sources more quickly and efficiently. This study aims to analyze the role of AI in Hadith takhrij and identify the opportunities and challenges arising from its implementation in the digital era. The research employs a library research method with a descriptive qualitative approach. Data were collected from various literature sources, including books, scientific journals, and scholarly articles related to AI and Hadith studies. The findings reveal that AI plays an important role in accelerating Hadith searches, identifying sanad and matan, classifying Hadith based on themes, and supporting the digitization of Hadith literature. Furthermore, AI offers opportunities to enhance research efficiency, develop interdisciplinary studies, and expand public access to Hadith knowledge. However, its application still faces several challenges, including limitations in data quality, difficulties in understanding the context of classical Arabic, and the inability to replace the critical analysis conducted by Hadith scholars. Therefore, AI should be utilized as a supporting tool that requires continuous academic supervision and verification.